Manajemen Laba Untuk Menghindari Penurunan Laba - Auliana, Rini Adriani; Wardi, Putri Amalia; Khairunnisa, Khairunnisa (CT. Rajawali media Utama, 2024)
This research aims to examine the type of earnings management used to avoid earnings decreases. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange during 2017-2020. The sampling technique used purposive sampling with a sample size of 102 companies and 408 observations during 4 years. The analysis technique uses multiple linear regression analysis. This research results real earnings management is used by managers to avoid earning decreases. The real earnings management method used by managers to avoid earning decreases is to increase the company's cash flow. Managers in manufacturing companies can increase company’s cash flow by manipulating sales such as giving discounts or extending credit terms.